Sustainability of the society through green human resources management practices: A proposed model - Nson, Yilkes Danladi (Goodwood Publishing, 2024)
Purpose: This study evaluates and fills this knowledge gap by providing empirical evidence of the relationship between green HRM practices and environmental performance based on the resource-based view, dynamic capabilities theory, and triple bottom line theory. Research Methodology: A detailed review of the empirical and conceptual articles related to this topic was conducted. An eclectic analysis and synthesis of evidence guided the development and presentation of the proposed framework. Results: A review of relevant studies revealed that GHRM practices positively determine society’s sustainability through the adoption of environmental practices. Green human resource management practices have also been proposed to have a direct link to society’s sustainability and an indirect link mediated by environmental practices. This study is limited to green human resource management practices, environmental practices, and the sustainability of society. Contribution: This study provides a valid mechanism and useful insights for corporate organizations, entrepreneurs, researchers/scholars, policy makers, community leaders, and government, among others, to facilitate the use of human resources (HRM) practices as a means for improving environmental practices and sustainability of society.